2012
DOI: 10.26634/jelt.2.4.2067
|View full text |Cite
|
Sign up to set email alerts
|

Powerpoint As A Potential Tool To Learners� Vocabulary Retention: Empirical Evidences from a Vietnamese Secondary Education Setting

Abstract: In Vietnamese secondary education, translation and visuals are traditionally used as major techniques in teaching new English lexical items. Responding to the Vietnamese government policy issued in 2008 on using IT for a quality education, the application of PowerPoint has been considered the most prevalent type of technology used in the classrooms throughout in Vietnam as Rickman (2000) stated. This paper reports the impact of implementing PowerPoint in teaching vocabulary in English classes in a Vietnamese s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In Vietnam, only a few studies deal with using PowerPoint presentations in teaching and learning languages. For example, Nam and Lap [23] study the impact of implementing PowerPoint in teaching vocabulary in English classes in a Vietnamese secondary education setting. The study, with a two-group pre-test and post-test design, aimed to test the effects of of PowerPoint-based materials in teaching and learning vocabulary.…”
Section: Previous Studies Related To the Current Researchmentioning
confidence: 99%
“…In Vietnam, only a few studies deal with using PowerPoint presentations in teaching and learning languages. For example, Nam and Lap [23] study the impact of implementing PowerPoint in teaching vocabulary in English classes in a Vietnamese secondary education setting. The study, with a two-group pre-test and post-test design, aimed to test the effects of of PowerPoint-based materials in teaching and learning vocabulary.…”
Section: Previous Studies Related To the Current Researchmentioning
confidence: 99%
“…A study by Nam and Trinh (2012) in two Vietnamese EFL secondary classrooms found the teacher's use of PowerPoints significantly increased English vocabulary learning by providing authentic material in a meaningful context involving sound, pictures, video, and animation. Creative use of PowerPoints in a storytelling approach to teaching English vocabulary significantly increased vocabulary learning of students 8 to 14 years old in a language center in Iran (Kalantar & Hashemian, 2015).…”
Section: Research On Multimedia Learning Of Vocabularymentioning
confidence: 99%